Purification by Affinity Chromatography and Properties of a β-Lactamase Isolated from Neisseria gonorrhoeae - Eriquez, Louis A. (1979)
β-Lactamase activity was detected in cell-free preparations obtained from ultrasonic treatment of Neisseria gonorrhoeae after growth in liquid medium. Crude preparations of β-lactamase were subjected to affinity chromatography, using several β-lactam antibiotics as ligands bound to agarose supports. Affinity gels produced by coupling 7-aminocephalosporanic acid or 6-aminopenicillanic acid by their amino groups to carboxyl-terminal agarose via a five- to eight-carbon spacer arm proved to be effective chromatography media. β-Lactamase preparations subjected to chromatography using these gels were purified 200-fold, with approximately 80% recovery of active material. Purified preparations were judged homogeneous by their behavior during electrophoresis on polyacrylamide in both the presence and absence of sodium dodecyl sulfate. Characterization of the purified enzyme established a molecular weight of approximately 25,000 and an isoelectric point of 5.4. Analyses of substrate specificity, effect of inhibitors, pH, and kinetic parameters were performed. The evidence suggests that the β-lactamase produced in N. gonorrhoeae closely resembles the character of class IIIa (TEM-type) β-lactamases.